PROSPECT OF UTILIZING EXPIRED HOMOLOGOUS PLATELET CONCENTRATES AS AN ALTERNATIVE SOURCE OF GROWTH FACTORS AND CYTOKINES IN CLINICAL SETUP FOR BETTER WOUND CARE AND HEALING - Adhya, Abhishek; Gayen, Soumya; Sow, Monoranjan; Das, Kalyan; Sarkar, Arindam (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The purposes of this study were: (1) To evaluate the possibility of preparation of human platelet lysate (hPL) from expired platelet concentrate, its storage – qualitative assessment in terms of growth factor content between freshly prepared hPL and preserved hPL (in liquid nitrogen for up to 6 months) and (2) to evaluate regenerative potential of the stored hPL on the 2° burn wound as compared to standard topical treatment for burns (1% silver sulfadiazine [SSD]). Methods: hPL was prepared by three rounds of freeze-thaw cycle; concentration of growth factors was estimated by enzyme-linked immunosorbent assay method and compared between fresh hPL and stored hPL. For clinical assessment, patients with 2° burn injury were randomly allocated to SSD and hPL treatment group. Wound status was compared on 3rd week by clinical assessments and based on histopathological findings. Immunohistochemistry was performed using cell proliferative markers to corroborate the extent of healing with the number of proliferating cells that give strong positive reactions to the markers. Results: Concentration of growth factors in tested samples (hPL fresh - <72 h, hPL-3 month and hPL-6 month) was almost same. No significant decrease in concentration was observed in any of the tested growth factor up to 6 months. p-values (analysis of variance) for concentration variations of platelet-derived growth factor-AA, basic-fibroblast growth factor,and transforming growth factor beta were 0.8981, 0.6417, and 0.9540, respectively. Healing of 2° deep-dermal burns was better for hPL group than SSD treatment at 3rd week and the observed tissue regeneration pattern was corroborated well with the expression of cell proliferative markers. Conclusion: Our findings suggest that hPL produced from expired platelet concentrates can be used as a potential source of biological factors that could serve its therapeutic need in the field of regenerative medicine, while on the other hand avoiding the waste of valuable human physiological resources.